Epigenetics in Neurodevelopment: Emerging Role of Circular RNA - Meng, Shujuan; Zhou, Hecheng; Feng, Ziyang; Xu, Zihao; Tang, Ying; Wu, Minghua (Frontiers in Cellular Neuroscience, 2019)
Canonical epigenetic modifications, including DNA methylation, histone modification and chromatin remodeling, play a role in numerous life processes, particularly neurodevelopment. Epigenetics explains the development of cells in an organism with the same DNA sequence into different cell types with various functions. However, previous studies on epigenetics have are only focused on the chromatin level. Recently, epigenetic modifications of RNA, which mainly include 6-methyladenosine (m6A), pseudouridine, 5-methylcytidine (m5C), inosine (I), 2’-O-ribosemethylation, and 1-methyladenosine (m1A), have gained increasing attention.Circular RNAs (circRNAs), which are a type of noncoding RNA without a 5’ cap or 3’ poly (A) tail, are abundantly found in the brain and might respond to and regulate synaptic function. Also, circRNAs have various functions, such as microRNA sponge, regulation of gene transcription and interaction with RNA binding protein.In addition, circRNAs are methylated by N6-methyladenosine (m6A). In this review, we discuss the crucial roles of epigenetic modifications of circRNAs, such as m6A, in the genesis and development of neurons and in synaptic function and plasticity. Thus, this type of changes in circRNAs might be a therapeutic target in central nervous system (CNS) disorders and could aid the diagnosis and treatment of these disorders.